The Clash Of Religious and Secular Views In Graham Greene's Works - Marifatkhon Boltabayeva (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
The purpose of this work is to identify the features of his writing strategy and ways of expressing the author's position. The object of study is the writer's novels, and the specific subject is the ways of expressing the author's position in them. For this purpose, a qualitative research strategy was chosen, which includes referencing, systematization and generalization of sources, their interpretation and critical evaluation, as well as plot analysis. The method of contextual analysis helps to consider the biographical, historical and literary context, which improves the understanding of the object under study. In this article, Graham Greene has extensively explored the concept of atheism through his works, expressing the dogmatic views of his characters. In addition, special attention is paid to the concept of "literary myth" in his works. It is expressed that in Graham Greene's novels, the fundamental differences between Christianity and Marxist atheism have disappeared